Narracje alternatywne i marginalne w uchwałach rocznicowych sejmu i senatu rzeczypospolitej polskiej w latach 2009-2019 - Bartłomiej Secler (Ksiegarnia Akademicka Publishing, 2021)
Alternative and Marginal Narrations in the Anniversary Resolutions of the Sejm and Senate of the Republic of Poland in 2009-2019. Example of Resolutions Commemorating the 70th and 80th Anniversaries of the Outbreak of the Second World War